P423 REACTION TIME IS CARE TIME: HOW TO ENSURE TO QUALITY AND SAFETY IN HEALTH CARE. (18th May 2022) - Boccini, V; Giannini, A; Tongiani, F; Ricci, T; Banti, S; Baratta, S
Abstract: Background: Caring cardiac and / or cardiac surgery patient requires specific and specialized skills. Interprofessional collaboration is needed along integrated care pathway. To improve innovation and quality of care services are important the multidisciplinary teamwork, customized patient interventions, continuing nursing training and the use of validated clinical tools shared between Healthcare Team. Nurses have a central role in terms of prevention: Patient monitoring system and multidimensional assessment allow to care and to identify ward patients who are in danger of clinical deterioration. That is important to ensure an appropriate management at an early stage. Clinical Case: On admission the patient is bright and alert and does not appear to be in distress. His vital signs are normal (MEWS 0). The patient is on therapy with Tirofiban and Furosemide in drips The diagnosis at admission is sub–occlusion of the Common Trunk of the Coronary Artery. After a few hours, the patient report retrosternal heartburn and dyspnoea with spontaneous regression. There aren't any significant alterations of clinical signs during the symptomatic phase (MEWS 0). However, the nurse decides to continue to monitor the person more frequently compared to the timing of MEWS Protocol. In a short time the nurse finds a progressive clinical instability of the patient, confirmed by an increase in MEWS score. Treatment: The patient monitoring system and the nursing process of Problem Solving and Decision Making allow to identify patient clinical deterioration at an early stage. For this reason, physicians and the critical care Team discuss about the management plan to guarantee of an appropriate care is provided. They decide to transfer the patient to the Intensive Care Unite, already intubated and ventilated. Conclusions: The reaction time is important to ensure quality and appropriateness of care, to minimize possible complications and to generate a positive impact on health outcomes, especially in the treatment of time–dependent disease. The experience is also important to promote the development of nurses' critical–thinking skills, competence and the ability to associate the use of clinical tools to the overall assessment of the person (medical history, clinical pathway and manifestations of the disease).